Gamma radiation shielding, fire resistance and physicochemical characteristics of Portland cement pastes modified with synthesized Fe2O3 and ZnO nanoparticles. (10th June 2018) - Abo-El-Enein, S.A.; El-Hosiny, F.I.; El-Gamal, S.M.A.; Amin, M.S.; Ramadan, M.
Highlights: Hematite nanoparticles enhance the mechanical properties of OPC pastes. Hematite nanoparticles improve the fire resistance and gamma radiation shielding of OPC pastes. ZnO nanoparticles act as a retarder for hydration reaction at room temperature. The retardation effect of ZnO nanoparticles could be eliminated at higher temperature. Abstract: This investigation aimed to utilize the synthesized hematite nanoparticles ( α -Fe2 O3 ) as well as ZnO nanoparticles (Wurtzite phase) for enhancing the mechanical properties, textural characteristics, thermal resistance and gamma radiation shielding of ordinary Portland cement pastes. Hematite nanoparticles (NF) and ZnO nanoparticles (NZ) were synthesized from 0.5 M FeCl3 ·6H2 O and 0.5 M zinc acetate di-hydrate (Zn(Ac)2 ·2H2 O), respectively in presence of specific cationic surfactant (CTAB). Characterization for the synthesized nanoparticles was performed by means of XRD, SEM, TEM, and EDX analyses. The particle diameters of the prepared NF and NZ were about 20 and 70 nm, respectively. 0.5, 1, 2 and 3% NF and 0.05, 0.1 and 0.2 NZ mass % of OPC were added to OPC. The physicochemical properties for the various investigated composites were examined at different hydration up to 90 days. After 28 days of hydration, the dried hardened specimens were fired to 300, 600 and 800 °C for 3 h to investigate fire resistance. Optimum additions of NF and NZ were 2 and 0.05%, respectively. Addition of 2% NF promoted gamma radiation shielding of OPC. On contrary, addition of 0.05% NZ had a negative effect on gamma radiation shielding of OPC. XRD, TGA/DTG and SEM results showed that various hydration products such as CSH, CAH, CASH and CFH were formed in presence of NF whereas; CSH and CZH were formed in presence of NZ. Results elaborated that NF had a good catalytic activity for hydration reaction whereas, NZ served as a retarder for hydration reaction.